Relationship Between Management of Working Asset and Firm Prof-itableness: (Case of Digi Telecom Berhad Malaysia) - Mohamed Ali Abdinur; Turan ÖNDEŞ (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2021)
The purpose of this study is to understand the association of proper management of working capital and profitableness of Digi telecom Berhad Malaysia during the period of 2015 until 2019. The methodology used is quantitative method statistics. In this paper, secondary data were used in a form of ratio analysis which is obtained from the financial reports of the past five years of Digi telecom. To investigate the strength and weakness of the correlation among working asset management and profitableness of the company correlation analysis, regression analysis and descriptive statistics were used. The findings indicate there is a solid negative correlation among return on asset to current ratio, quick ratio and day’s payable outstanding whereas there is moderate and weak negative relationship between return on asset to debtors turnover ratio and inventory turnover ratio respectively. It is important for managers of Digi telecom to create and improve the shareholders wealth and value by improving the company’s working capital ratio and reduce the days collection period and days payable outstanding. Keywords: Working capital management, firm profitability, business performance